Characterization Analysis of the Main Character in “Hichki” Movie - Tira Nur Fitria (Vivid: Journal of Language and Literature, 2021)
Characterization is the author’s effort in presenting the character of the characters. It is made to build and develop the characters in a story. This characterization is related to the attitudes, desires, interests, emotions, and moral principles of the characters. This characterization also suggests the embodiment and development of the characters in the story. The objectives of this research are to analyze the characterization of the main characters in “Hichki” movies. The approach used in this analysis is descriptive qualitative research, the research data are from dialogues between characters in the movie that are linked to character characterization. The results of this research show that Naina Mathur is the main character or central figure in the “Hichki” movie. She is Tourette’s syndrome sufferer. The characterizations are educated woman, always keep the spirit and never give up, have confidence, stands to belief and stick to the principles, protective, optimistic, creative, responsible, and being a good teacher. This movie shows the character of Naina Mathur as a teacher who is rarely found in educational circles. Like teachers who are challenged to guide their students to develop according to their respective talents. Naina Mathur is a central character where her character becomes the essence as well as the beginning until the ending of the story.